Pretreatment with serine protease inhibitors impairs Leishmania amazonensis survival on macrophages - Patrícia de Almeida Machado; Pollyanna Stephanie Gomes; Elaine Soares Coimbra; Herbert Leonel de Matos Guedes (Parasites & Vectors)
Abstract Background Leishmaniases are neglected tropical diseases with great clinical and epidemiological importance. The current chemotherapy available for the treatment of leishmaniasis presents several problems, such as adverse effects, toxicity, long treatment time, and parasite resistance. The discovery of new therapeutic alternatives is extremely essential, and the discovery of cellular targets is a tool that helps in the development of new drugs. Serine proteases emerge as important virulence factors in the Leishmania genus, as they participate in important processes involved in their infectivity, virulence, and survival. In this work, we evaluated the leishmanicidal effect of different serine protease inhibitors (Benzamidine, PF-429242, PMSF, TLCK, and TPCK). Additionally, we determined the implication of pretreatment with these inhibitors on the entry and survival of parasites within macrophages, as well as the conversion of promastigotes into amastigotes, to discover the importance of serine proteases in the establishment of infection and, consequently, as targets for new drugs for Leishmania. Results In general, the inhibitors had low toxicity in host macrophages, and three showed some effect in promastigote and amastigote forms of L. amazonensis (PF-429242, TLCK, and TPCK). Using a short incubation interval, we pretreated L. amazonensis promastigotes with these five compounds before in vitro infection. Pretreatment with PF-429242, TLCK, and TPCK considerably compromised the survival of these parasites inside host macrophages, without altering the entry of promastigotes into these cells and differentiation into amastigotes. In addition, treatment with PF-429242 and TPCK was able to reduce the serine proteases’ enzymatic activity using subtilisin substrate on L. amazonensis promastigote lysate. Conclusions This work highlights the importance of serine proteases in L. amazonensis as a possible target for new therapeutic alternatives in Leishmania spp. Graphical Abstract